American spaces of conversion the conductive imaginaries of Edwards, Emerson, and James - Knutson, Andrea (New York ; Oxford : Oxford University Press, 2011)
This study examines how the concept of conversion and the legacy of the doctrine of preparation, as articulated in Puritan Reformed theology and transplanted to the Massachusetts Bay colony, remained a vital cultural force shaping developments in American literature, theology, and in philosophy in the form of pragmatism.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Conversion -- Christianity; Puritans -- Doctrines; Puritans -- Influence; Edwards, Jonathan, -- 1703-1758.; Emerson, Ralph Waldo, -- 1803-1882.; James, William, -- 1842-1910.